2015
DOI: 10.1007/978-3-319-26925-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Group-Based Communication in WhatsApp

Abstract: This work investigates group-based communication in Whats-App based on a survey and the analysis of messaging logs. The characteristics of WhatsApp group chats in terms of usage and topics are outlined. We present a classification based on the topic of the group and classify anonymized messaging logs based on message statistics. Finally, we model WhatsApp group communication with a semi-Markov process, which can be used to generate network traffic similar to real messaging logs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Findings underscore the importance of WhatsApp in disseminating messages in group-based communication. This result agrees with Shahid (2018) and Seufert et al (2015) who found that WhatsApp has become vital for group-based communication. As evident in Table 3, a total of 20 posts were recorded over the three months, with comment having the highest number 9(45.0%), text followed with 7(35.0%) messages and link had 4(20.0%).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Findings underscore the importance of WhatsApp in disseminating messages in group-based communication. This result agrees with Shahid (2018) and Seufert et al (2015) who found that WhatsApp has become vital for group-based communication. As evident in Table 3, a total of 20 posts were recorded over the three months, with comment having the highest number 9(45.0%), text followed with 7(35.0%) messages and link had 4(20.0%).…”
Section: Resultssupporting
confidence: 92%
“…Several scholars have investigated WhatsApp as a communication tool. Seufert et al (2015) investigated group-based communication in WhatsApp. They found that the app has become an important means of communication.…”
Section: Whatsapp: Information or Misinformation Gateway For Covid-19?mentioning
confidence: 99%
See 1 more Smart Citation
“…We should emphasize the fact that WhatsApp is considered by the participants of our sample as an assistance in quick communication of trivial information, which does not imply it is dispensable or useless. On the contrary, this type of information is extremely useful to successfully organize all the tasks and activities that fill a great part of our everyday life [57].…”
Section: Discussionmentioning
confidence: 99%
“…Outra dentre as principais características que diferem o WhatsApp das mensagens de texto SMS está na ferramenta de criação de grupos. Desta forma, alguns estudos estão voltados em como se dá essa comunicação baseada em grupos dentro do WhatsApp [Seufert et al 2015, Seufert et al 2016. [Rosenfeld et al 2018] realizaram uma análise do comportamento de 100 usuários para inferência de informações demográficas como idade e gênero.…”
Section: Trabalhos Relacionadosunclassified